Odpowiedź :
Odpowiedź:
a)
7*x - 5 = 4
7x - 5 = 4
7x = 4 + 5
7x = 9 / :7
x = 9/7
spr
7 * 9/7 - 5 = 4
9 - 5 = 4
4 = 4
b)
m - 4 = 8
m = 8 + 4
m = 12
spr
12 - 4 = 8
8 = 8
c)
x * 2 = 8
2x = 8 / :2
x = 4
spr
2 * 4 = 8
8 = 8
d)
0,1 * x + 7 = 11
0,1x + 7 = 11
0,1x = 11 - 7
0,1x = 4 / : 0,1
x = 40
spr
0,1 * 40 + 7 = 11
4 + 7 = 11
11 = 11
e)
6 * k + 3 = 33
6k + 3 = 33
6k = 33 - 3
6k = 30 / : 6
k = 5
spr
6* 5 + 3 = 33
30 + 3 = 33
33 = 33
f)
s - 9 = 6
s = 6 + 9
s = 15
spr
15 - 9 = 6
6 = 6
Szczegółowe wyjaśnienie:
Odpowiedź:
a)
7*x - 5 = 4
7x = 4 + 5 /:7
x = 9/7 = 1 2/7
spr.
L = 7 * 9/7 - 5 = 9 - 5 = 4
P = 4
L = P
b)
m - 4 = 8
m = 8 + 4 = 12
spr.
L = 12 - 4 = 8
P = 8
L = P
c)
x * 2 = 8 /:2
x = 8/2 = 4
spr.
L = 4 * 2 = 8
P = 8
L = P
d)
0,1 * x + 7 = 11
0,1x = 11 - 7 /:0,1
x = 4/0,1 = 40
e)
6 * k + 3 = 33
6k = 33 - 3 /:6
k = 30/6 = 5
spr.
L = 6 * 5 + 3 = 30 + 3 = 33
P = 33
L = P
f)
s - 9 = 6
s = 6 + 9 = 15
spr.
L = 15 - 9 = 6
P = 6
L = P
Szczegółowe wyjaśnienie: